Optimalisasi Akuntabilas dan Transparansi Pengelolaan Dana Desa dalam APBN 2025 - Putri, Elivia Pasma (CV. Kurnia Grup, 2025)
The rapid development of technology and information indirectly demands that Indonesia's governance system run optimally. This certainly requires the government to increase accountability and transparency in all aspects, including finance. Accountability and transparency are fundamental requirements to prevent abuse of power and to ensure that state finances are directed towards achieving national goals more effectively and efficiently. This step can begin at a smaller level or scale, namely through the management of village funds. Optimal management of village funds is crucial to ensuring that government performance aligns with the results achieved. The author's research used a qualitative research method through a literature study approach, gathering all relevant information on the problem being studied through other literature such as books, journals, articles, and previous research. Through this research, readers are expected to understand how accountability and transparency in village fund management, what indicators of successful village fund management are, and how to optimize the management of accountability and transparency in the 2025 State Budget.